Removal of Heavy Metal Ions Using Pristine and Functionalized Natural Zeolites - Khoirul Ihsan Solihin; St Mardiana; Handajaya Rusli; Grandprix Thomryes Marth Kadja (Universitas Gadjah Mada, 2023)
Heavy metal ions have attracted significant concern regarding their toxicity in living organisms. Concurrently, the removal of heavy metals by the adsorption method is also under the spotlight because it is effective, less cost-demanding, and easy to operate. To date, natural zeolites become one of the most used adsorbents for it is low cost, abundant in reserve, and has high selectivity towards heavy metal. Zeolites possess negatively charged three-dimensional frameworks built by SiO4 and AlO4 tetrahedra, which are balanced by counter-cations. The cations within zeolite frameworks can be exchanged with the heavy metal cations in an aqueous environment. This review comprehensively reports the adsorption capacity of heavy metal ions using pristine and modified natural zeolite. The important aspects, including the physicochemical properties of pristine and modified natural zeolites, heavy metal ion adsorption isotherms, kinetics, and thermodynamics, are discussed in detail. It is imperative to note that the physicochemical properties of natural zeolites greatly determine the adsorption capability. Furthermore, natural zeolites could be modified with various molecules such as surfactants and polymers to improve the adsorption capacity and adsorb heavy metal anions. Ultimately, this review is concluded with prospects for future improvement.